System of methodological procedures for the professional training of the health rehabilitator in Occupational Therapy - Pedro Oropesa Roblejo; Yumisleydis Salgado Facundo; Isis García Wilson (Centro Provincial de Información de Ciencias Médicas, 2019)
Keeping in mind the scarce updating level of the health rehabilitator in Occupational Therapy, which is against the care to patients with disabilities, a system of methodological procedures was elaborated that will facilitate the acquisition, amplification and continuous improvement of knowledge and necessary skills for a better acting in the comprehensive rehabilitation, starting from the scientific-technological-assistance character in this process.